A Novel, 5-Transcript, Whole-blood Gene-expression Signature for Tuberculosis Screening Among People Living With Human Immunodeficiency Virus - Rajan, Jayant V (Clin Infect Dis, 2019)
BACKGROUND: Gene-expression profiles have been reported to distinguish between patients with and without active tuberculosis (TB), but no prior study has been conducted in the context of TB screening. METHODS: We included all the patients (n = 40) with culture-confirmed TB and time-matched controls (n = 80) enrolled between July 2013 and April 2015 in a TB screening study among people living with human immunodeficiency virus (PLHIV) in Kampala, Uganda. We randomly split the patients into training (n = 80) and test (n = 40) datasets. We used the training dataset to derive candidate signatures that consisted of 1 to 5 differentially-expressed transcripts (P ≤ .10) and compared the performance of our candidate signatures with 4 published TB gene-expression signatures, both on the independent test dataset and in 2 external datasets. RESULTS: We identified a novel, 5-transcript signature that met the accuracy thresholds recommended for a TB screening test. On the independent test dataset, our signature had an area under the curve (AUC) of 0.87 (95% confidence interval [CI] 0.72–0.98), with sensitivity of 94% and specificity of 75%. None of the 4 published TB signatures achieved desired accuracy thresholds. Our novel signature performed well in external datasets from both high (AUC 0.81, 95% CI 0.74–0.88) and low (0.81, 95% CI 0.77–0.85) TB burden settings. CONCLUSIONS: We identified the first gene-expression signature for TB screening. Our signature has the potential to be translated into a point-of-care test to facilitate systematic TB screening among PLHIV and other high-risk populations.